THE SIGNIFICANCE OF THE METHODOLOGY OF THE WORLD MUSIC EDUCATION SYSTEM - Kavilova Dilyorakhan Abdujabbar qizi (American Journals Publishing, 2024)
This article is devoted to the compatibility and relevance of the world system of music education with the standards of our republic. It talks about the importance of methodology, system and theories of the world system of music education. According to the results of studies conducted by a number of scientists, the effects of music and rhythms on the human body and psyche, and the functions of art have been described. Conclusions and proposals are presented about the positive aspects of the functional music, which is a new sphere of music today.
Keywords: Music education, system, methodology, theory, musical upbringing, creative abilities, harmony, pedagogical technology, process, specialty.